Situational tests in student selection: An examination of predictive validity, adverse impact, and construct validity - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2002)
The Flemish Admission Exam 'Medical and Dental Studies' is comprised of four cognitive ability tests and four situational tests, namely two work samples (i.e., a lecture and a medical text) and two video-based situational judgement tests (i.e., a physician-patient interaction and a medical expert discussion). On the basis of the Admission Exam scores of 941 candidates (359 men, 582 women) this study shows that situational tests significantly can predict better than cognitive ability tests, with lecture and text emerging as significant predictors. When situational tests are combined with cognitive ability tests, there are no mean gender differences. Situational tests also enable us to measure a broader range of constructs. For example, in this study, the personality factor Openness is related to better situational test performance. Overall, this study demonstrates that situational tests may be a useful complement to traditional student selection procedures.